Beta decay studies with total absorption spectroscopy and the Lucrecia spectrometer at ISOLDE *This article belongs to the Focus on Exotic Beams at ISOLDE: A Laboratory Portrait special issue. (30th June 2017) - Rubio, B; Gelletly, W; Algora, A; Nacher, E; Tain, J L
Abstract: Here we present the experimental activities carried out at ISOLDE with the total absorption spectrometer Lucrecia, a large 4 π scintillator detector designed to absorb a full gamma cascade following beta decay. This spectrometer is designed to measure β -feeding to excited states without the systematic error called Pandemonium . The set up allows the measurement of decays of very short half life. Experimental results from several campaigns, that focus on the determination of the shapes of β -decaying nuclei by measuring their β decay strength distributions as a function of excitation energy in the daughter nucleus, are presented.